ENVIRONMENTAL QUALITY OF SURFACE SEDIMENTS IN THE SOUTH OF NHA TRANG BAY - Vinh, Le Thi; Tam, Pham Huu (Vietnam Journal of Marine Science and Technology, 2015)
Analyzed results of 11 surface sediment samples collected in June 2012 in the south of  Nha Trang bay showed that: The contents of the organic materials and heavy metals in the sediments were considerably various (organic C: 0.12 - 1.46% , organic N: 135.8 - 987.7 µg/g, total P: 44.0 - 551.1 µg/g; Zn: 2.2 - 28.7 µg/g; Cu: 2.6 - 22.2 µg/g, Pb: 2.7 - 28.1 µg/g, Fe: 514 -         17,337 µg/g) and correlated with the rate of mud fraction; Organic carbon and heavy metal contents tended to be higher in areas near Tre and Tam Islands and lower value in off - shore areas; Among studied areas: i) There was no significant difference in hydrocarbon content (from 115 - 188 µg/g); ii). Related to microbiology, coliform density (from 0 - 8,197 MPN/100g) was highest at Mieu and Mot Islands. Generally, the surface sediments in Nha Trang bay, in terms of organic materials and heavy metals, were suitable for the aquatic life. However, there was the lightly increasing trend in organic matters (N and P) from 2007 to 2012.